1999
DOI: 10.1021/ol990155f
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient New Route to Tetradentate and Pentadentate Macrocyclic Tetraamide Ligands

Abstract: A crucial diamide diamine intermediate in the synthesis of tetradentate macrocyclic tetraamide ligands protected against oxidative decomposition has been synthesized without the use of potentially hazardous organic azide intermediates. This intermediate has also been used to synthesize a new class of pentadentate macrocyclic tetraamide ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Amidopyridine macrocycle H 2 pydioneN 5 (Scheme ) and its analogues have been prepared previously, ,, but its complexation with transition metal ions has not been studied. We found that anhydrous iron(III) chloride readily reacts with H 2 pydioneN 5 at ambient temperature in the presence of 2 equiv of triethylamine, yielding an iron(III) complex with a doubly deprotonated ligand, [Fe(pydioneN 5 )Cl(H 2 O)].…”
Section: Resultsmentioning
confidence: 99%
“…Amidopyridine macrocycle H 2 pydioneN 5 (Scheme ) and its analogues have been prepared previously, ,, but its complexation with transition metal ions has not been studied. We found that anhydrous iron(III) chloride readily reacts with H 2 pydioneN 5 at ambient temperature in the presence of 2 equiv of triethylamine, yielding an iron(III) complex with a doubly deprotonated ligand, [Fe(pydioneN 5 )Cl(H 2 O)].…”
Section: Resultsmentioning
confidence: 99%
“…Ethyl 4-aminocinnamate ester building blocks C , D , and E were obtained by condensation of ethyl 4-aminocinnamate with amino acid chlorides 18 , themselves obtained from commercially available amino acids using the procedure of Rorrer et al, as shown in Scheme . Fragment H was prepared in a similar fashion starting from α-methylcinnamic acid 19 via sequential protection of the acid function and reduction of the nitro group to give aniline 20 .…”
Section: Chemistrymentioning
confidence: 99%